Synthesis and Structural Characterization of Cu(II) Complexes of 2-Arylhydrazono-1-Phenylamino Butane-1,3-Dione - Srivastava, S.; Manisha Agnihotri, Ms. (Asian Journal of Chemistry, 2010)
Cu(II) complexes of 2-aryIhydrazono-1-phenylamino butane-1,3-dione (AHPABD) having substituents H, 2-NO2, 3-NO2, 4-NO2, 4-CH3, 3-CI in the phenyl ring have been prepared and characterised by elemental analysis, IR and electronic spectral studies. The analytical results suggest that complexes are formed in 1: 2 (M: L) ratio and are isostructural in which AHPABD acts as bidentate ligand.